'Bitterness towards Egypt' – the Moroccan nationalist movement, revolutionary Cairo and the limits of anti-colonial solidarity. Issue 2 (2nd April 2016) - Stenner, David
Abstract: This articles analyses the campaign conducted by the Moroccan nationalist movement in Cairo after World War II aiming to enlist the Arab League in its anti-colonial struggle. Although the Maghribi activists initially celebrated several successes, they ultimately failed to obtain any diplomatic support, especially following the Egyptian revolution of 1952. Drawing on Moroccan as well as French, Spanish, and US sources, this article argues that Nasser and his colleagues refused to support the Moroccans due to irreconcilable ideological differences, thus laying the foundation for the scepticism towards the Arab world that characterised Morocco's foreign policy during the Cold War.